Analisis Kadar Kalsium, Kalium, Besi Akibat Variasi Waktu Rendam Kacang Produksi Susu Almond secara Spektrofotometri Serapan Atom - Yade Metri Permata; Suprianto; Ananda Sri Devy (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Background: Calcium, potassium and iron can be obtained from milk, nuts, eggs, fish, fruit vegetables, green vegetables and products needed by the human body which play a role in maintaining body functions, including cells, tissues, organs and overall function. Objective: Research to determine the levels of these minerals in almond milk using atomic absorption spectrophotometry (AAS). Method: Almonds were soaked for 4, 8, and 12 hours respectively for almond milk 1, 2, and 3 (SA1, SA2, and SA3) and Almendrola packaged milk (SA4). Samples were wet digested with concentrated HNO3. Analysis of calcium, potassium and iron levels using AAS with an air-acetylene flame was 422.7; 766.5; and 248.3 nm for calcium, potassium and iron respectively. Validated methods include accuracy, precision, LOD and LOQ. Results: Results of determining the mineral content of almond milk (mg/100g) for calcium, potassium and iron respectively (2.6551 ± 0.0925; 5.5464 ± 0.3178; 5.8866 ± 0.03805; and 4.5842 ± 0.2590), (2.4096 ± 0.0551; 2.5150 ± 0.0115; 2.6551 ± 0.0557; and 2.5150 ± 0.0551), and (0.3202 ± 0.0282; 0.3307 ± 0.0048; 0.3344 ± 0.011; and 0.3183 ± 0.0045). Conclusion: Validation of the method meets the requirements, soaking impacts increasing mineral levels in Almond Milk, and there are significant differences in calcium, potassium and iron levels in the milk.